PENGARUH PENYULUHAN DAN PELATIHAN MENYIKAT GIGI TERHADAP PERILAKU MENYIKAT GIGI PADA PENYANDANG TUNADAKSA DI YAYASAN CAHAYA MUTIARA UBUD, KECAMATAN TAMPAKSIRING KABUPATEN GIANYAR - Anak Agung Gede Agung; I Nyoman Wirata; I G A Raiyanti; Ni Nyoman Widiari (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Dental and oral disease is a public health problem today, especially periodontal tissue disease and dental caries. Both of these diseases will be able to cause interference with the function of mastication, so that it can interfere with the process of digestion and absorption of food. Statistics show that dental and oral disease affects almost everyone, including people with disabilities, including the physically disabled group. The purpose of this study was to analyze the effect of knowledge on tooth brushing behavior of people with disabilities at the Cahaya Mutiara Foundation Ubud, Tampaksiring District, Gianyar Regency in 2020. The research method was Pre and Post tests, which were tested with a one sample test from Wilcoxon. The results showed that the higher the target's knowledge of how to take care of teeth, the better the target's behavior for brushing teeth. The statistical test showed that there was a significant effect on increasing knowledge before and after being given counseling, namely the P value of 0.00. The conclusion is that there is a significant effect on increasing knowledge before and after being given counseling, namely the P value of 0.00. It is recommended to keep  until their behavior is formed into a habit that supports dental and oral health.